Self-based learning fuels social-based learning—but not the other way around: insights from a cross-lagged panel study on informal workplace learning - Decius, Julian; Knappstein, Michael; Seifert, Andreas (Frontiers in Organizational Psychology, 2025)
IntroductionAccording to conceptual research on informal learning, the dimensions of the multidimensional construct of informal workplace learning (IWL) interact dynamically. This study adopts a conservation of resources perspective to empirically examine the largely unexplored assumption that self-based IWL (i.e., experimentation and reflection) and social-based IWL (i.e., feedback seeking and modeling) are interrelated over time.MethodsUsing a three-wave survey design with a four-week lag, the study analyzed data from a final sample of 321 employees.ResultsFindings from a structural equation model employing a cross-lagged panel design indicate that self-based IWL is consistently and significantly positively related to social-based IWL over time. However, contrary to expectations, no significant time-lagged association was found in the reverse direction, from social-based IWL to self-based IWL.DiscussionOverall, this evidence suggests that engaging in self-based IWL may act as a catalyst for employees to pursue social-based IWL opportunities, whereas relying primarily on social-based IWL does not appear to stimulate further self-based IWL. The findings provide novel insights into the sequential dynamics of IWL dimensions and have important implications for the design of workplace learning interventions aimed at fostering sustainable learning processes.